Pembelajaran Mikrokontroler yang Interaktif Menggunakan Tinkercad di SMK NU 1 Islamiyah Kramat Kabupaten Tegal - Eko Budihartono; Lukmanul Khakim; Ida Afriliana; Ahmad Maulana; Rais Rais; Eko Budiraharjo (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Tinkercad is a web-based platform that allows users to design in the fields of electronics and coding. The platform offers various simulation components to support planning and procurement of necessary components. The community service activity took place on May 28, 2024, starting from 10:30 AM to 12:00 PM local time. The event was attended by 31 students from SMK NU 1 Islamiyah Kramat, Tegal Regency, consisting of 10th and 11th grade students majoring in Computer Networking Engineering (TKJ). The challenge faced during this community service activity was the students' lack of knowledge in using Tinkercad for electronic design and coding. The aim of the community service was to enhance the understanding of SMK students about Tinkercad application. The method employed was an interactive workshop lasting for 2 hours with 31 TKJ students. Evaluation was conducted through pre-tests, post-tests, and questionnaires. The results achieved: 100% of students admitted to never having used Tinkercad before. After the workshop, 100% of students reported finding it easy to understand and follow the training. The results indicated a significant improvement in their understanding of Tinkercad usage.